FOOD ALLERGENS - PRESENCE, RISKS AND MANAGEMENT IN FOOD INDUSTRY - Grujić, R. (Journal of Engineering & Processing Management, 2015)
Food allergy is a reaction of the body immune system to the presence of the proteins in the body introduced through food. Allergic reactions can affect the skin (hives), gastrointestinal organs (nausea, cramps, diarrhea), respiratory system (attenuation) and circulation (drop in blood pressure). In extreme cases, anaphylaxis can occur.. In this case, death can occur within minutes. Food allergens are natural proteins that are resistant to the action of heat, proteolytic enzymes, and pH change. The immune system of an individual may react in a very small amount of allergen present (the amount expressed in ppm). Different individuals have different levels of sensitivity and specific response to the presence of the same allergen. Avoiding contact with the allergen is the only way a person can prevent allergic reactions. An estimated 2-4% of the total population in Europe, 4-8% of children and 1-2% of adults in the US have food allergies. Allergic reactions to food in the United States are causing 150-200 deaths per year. Reducing the risk of food elergene faced by consumers can be mitigated by timely identification of food products that contain substances causing allergic reactions, adequate control of the manufacturing process and storage of food (GMP, HACCP) and the use of tools that can be conducted to verify the control (regulations, labeling).